Adolescents' proxy reports on obesity-related parenting practices: factorial validity and reliability across four behavioral domains - Gabriel L. Fuligni; Christopher J. Gonzalez; Roger Figueroa (BMC, 2022)
Abstract Background Adolescents' energy balance behaviors are precursors to obesity shaped by the practices or strategies that many parents implement. Although key stakeholders to their families, adolescents are rarely considered to report on these obesity-related parenting practices. The aim of this study is to assess the factorial and predictive validity of adolescents' proxy-report of parents' obesity-related parenting across four behavioral domains. Methods This study used data from the Family Life, Activity, Sun, Health, and Eating (FLASHE) study. This study tests whether adolescents' proxy reports about their parents' obesity-related parenting are significantly associated with parents' responses on their own obesity-related parenting, as well as whether these reports are significantly associated to parent-adolescent energy balance behaviors. Factorial validity was assessed using linear regression and Confirmatory Factor Analysis (CFA), whereas predictive validity was assessed using Actor-Partner Interdependence Modeling (APIM). Results Regression results indicated that adolescents' proxy report is significantly associated with parents' report of their own parenting in all four domains (β = .59-.71; p < 0.05). CFA results indicated a final factor structure that loaded significantly onto hypothesized obesity-related parenting domains (β > .30) in both adolescents and parents. APIM results indicated that both parent- (β = .32; p < 0.05) and adolescent-(β = .21; p < 0.05) reported obesity parenting for fruit and vegetable consumption were associated with their own fruit and vegetable intake. In addition, adolescent-reported physical activity parenting was significantly associated with adolescent physical activity (β = 0.23; p < 0.05). Regarding partner effects, only parent-reported parenting for fruit and vegetable consumption were significantly associated with adolescent intake of fruit and vegetables (β = 0.15, p < 0.05) and adolescent-reported physical activity parenting was significantly associated with parental physical activity (β = 0.16, p < 0.05). Neither adolescent nor parent reported parenting were significantly associated with screen time or junk food intake outcomes. Each final obesity-related parenting scale had good internal consistency (a = .74-.85). Conclusions We found that adolescent- and parent-reported obesity-related parenting were significantly associated, while adolescent-reported parenting were more explanatory of fruit and vegetable intake and physical activity than parent-reported parenting. These findings suggest that adolescent proxy reports may be a valid source of information on obesity-related parenting.